2015
DOI: 10.15288/jsad.2015.76.635
|View full text |Cite
|
Sign up to set email alerts
|

“Hey Everyone, I’m Drunk.” An Evaluation of Drinking-Related Twitter Chatter

Abstract: ABSTRACT. Objective: The promotion of drinking behaviors correlates with increased drinking behaviors and intent to drink, especially when peers are the promotion source. Similarly, online displays of peer drinking behaviors have been described as a potential type of peer pressure that might lead to alcohol misuse when the peers to whom individuals feel attached value such behaviors. Social media messages about drinking behaviors on Twitter (a popular social media platform among young people) are common but un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 30 publications
7
102
0
9
Order By: Relevance
“…Our finding that most posts related to substances were positive is consistent with previous studies [7,[13][14][15][16]. A selection bias exists in the present data, as these attitudes may not be consistent with the majority of college students, but the findings highlight the type of content to which any college student may be exposed to via social media.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding that most posts related to substances were positive is consistent with previous studies [7,[13][14][15][16]. A selection bias exists in the present data, as these attitudes may not be consistent with the majority of college students, but the findings highlight the type of content to which any college student may be exposed to via social media.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, exposure to substance use via social media normalizes the use for some young adults, and can present the subject in a positive light, potentially providing a skewed perspective compared to the behavior of most college-aged persons. In fact, a study involving the social networking site Twitter showed that messages ("tweets") about alcohol use (especially heavy use and binge drinking) are quite common, and typically portray a positive attitude about the substance (pro-alcohol tweets were ten times more frequent than antialcohol tweets; [7]). …”
Section: Introductionmentioning
confidence: 99%
“…An earlier US study found 93 commercial Facebook pages with more than one million "friends" for top beer brands and 334 pages with more than three million for top spirit brands, with a vast array of applications and activities available through or promoted on these pages (Mart, Mergendoller, & Simon, 2009). A search of drinkingrelated content on Twitter identified 11,966,381 English-language tweets in a one-month period in 2014; the most common keyword was "drunk" (5,336,372), followed by "beer" (3,444,778) and "alcohol" (1,565,258) (Cavazos-Rehg, Krauss, Sowles, & Bierut, 2015). Analysis of a random sample of 5,000 of these tweets identified that 16% were commerciallygenerated marketing or promotion.…”
Section: The Extent and Nature Of Alcohol Marketing On Social Mediamentioning
confidence: 99%
“…A study of Twitter found that the majority of content was positive towards alcohol and that most content was generated by individual users rather than companies or corporations (Cavazos-Rehg, Krauss, Sowles, & Bierut, 2015). Previous studies in other health-related areas have illustrated that Twitter can be used to identify alcohol-related behaviors or intentions across populations (Chew & Eysenbach, 2010;Signorini, Segre, & Polgreen, 2011).…”
Section: User-generated Alcohol Contentmentioning
confidence: 99%